Effect of conbercept or ranibizumab in the treatment of wet age-related macular degeneration - Dawei Zhang; Zahrah Khan; Tao Chai (Wolters Kluwer Medknow Publications, 2019)
Objective: The aim of this study was to investigate the effects of conbercept or ranibizumab in the treatment of wet age-related macular degeneration (AMD) and to explore the influence on central retinal thickness (CRT), visual acuity, and choroidal neovascularization (CNV) permeation. Patients and Methods: A total of 85 patients (85 eyes) with wet AMD were enrolled in this study. All patients were treated by intravitreal injection of anti-vascular endothelial growth factor and were randomly divided into two groups. Patients in Group A were treated by intravitreal injection of conbercept, whereas those in Group B were treated by intravitreal injection of ranibizumab once a month for 3 consecutive months. The best-corrected visual acuity (BCVA) was measured. Subfoveal choroidal thickness (SFCT) and CRT of affected eyes and healthy eyes were examined with optical coherence tomography. Fundus fluorescein angiography was performed, and the area of CNV permeation was calculated. Results: BCVA (logarithm of the minimum angle of resolution) of affected eyes in the two groups was significantly better at 1 month, 2 months, and 3 months after treatment as well as at the end of follow-up than that of before treatment. Meanwhile, CRT was obviously decreased. SFCT of affected eyes was significantly smaller than that of before treatment, which was also remarkably smaller when compared with that of healthy eyes. At 3 months after treatment and at the end of follow-up, the areas of CNV permeation in the two groups were significantly decreased. In addition, the average times of injection in Group A were significantly less than that of Group B. Conclusions: Intravitreal injection of conbercept and ranibizumab significantly decreased SFCT of affected eyes. However, the length of conbercept medication injection time was lower than that of ranibizumab.